Ethical Issues in Using Jasper AI and Scribbr for Academic Writing among University Students - Agung Rinaldy Malik (Journal of Innovative and Creativity, 2025)
The growing adoption of artificial intelligence (AI) tools in higher education has transformed students’ approaches to academic writing. This study investigates the ethical issues arising from the use of Jasper AI and Scribbr among Indonesian university students. Employing a qualitative descriptive design, semi-structured interviews were conducted with sixteen students from diverse disciplines alongside a review of institutional documents. Thematic analysis revealed three main findings: (1) students commonly use Jasper AI for idea generation and drafting while relying on Scribbr for plagiarism checking and proofreading; (2) although these tools enhance writing efficiency and confidence, they also raise concerns about overdependence and diminished critical thinking; and (3) there is limited awareness and inconsistent understanding of institutional guidelines regarding AI-assisted writing, leading to blurred ethical boundaries. These findings highlight an urgent need for universities to update academic integrity policies and integrate AI ethics education into writing instruction. By addressing these gaps, higher education institutions can support responsible and informed use of AI tools while safeguarding the core values of academic honesty and originality.